Effects of aeration on microbes and intestinal bacteria in bioaerosols from the BRT of an indoor wastewater treatment facility - Wang, Yanjie; Li, Lin; Xiong, Ren; Guo, Xuesong; Liu, Junxin (The Science of the total environment, 2019)
The generation and emission of airborne bacteria from a biochemical reaction tank (BRT) for wastewater treatment was investigated by altering the aeration rate. The levels of bioaerosols increased from 715 ± 69 to 1597 ± 135 CFU/m3 (total airborne bacteria) and from 78 ± 6 to 359 ± 18 CFU/m3 (intestinal bacteria) as the aeration rate increased from 0.3 to 1.2 m3/h. Most airborne bacteria were attached to particles smaller than 4.7 μm at an aeration rate of 0.3 m3/h. They were found attached to larger particles (>4.7 μm) when the aeration rate increased to 1.2 m3/h. A similar phenomenon was observed for intestinal bacteria. The high-throughput sequencing technique was used to assay the microbial populations of the bioaerosols. Both microbial counts and diversity increased as the aeration rate increased. Brevundimonas (63.82%), Chryseobacterium (16.54%), and Micrococcaceae (12.37%) were the dominant intestinal bacteria at an aeration rate of 0.3 m3/h. Pseudochrobactrum (33.10%), Citrobacter (21.28%), and Yersinia (18.21%) were the dominant intestinal bacteria at an aeration rate of 1.2 m3/h. The level, particle size distribution, population structure, and diversity of the bioaerosols were all affected by aeration rate. The source tracker results indicated that water and the surrounding air were the two main bioaerosol sources. The contribution of water is greater at larger levels of aeration. Inhalation was the main pathway of microbial aerosol intake for people in the surrounding area. The exposure hazard quotients for adult males were generally higher than those for adult females. Necessary measures should be taken to ensure worker safety. [Display omitted] •Generation and emission of airborne bacteria during microporous aeration•Source tracker indicated water and ambient air were sources of airborne bacteria.•Microbial counts and diversity increased as the aeration rate accelerated.•Intestinal bacteria presented in the bioaerosols.•Health risks of intestinal bacteria in bioaerosols are greater than general bacteria.